Somewhat $ω$-continuous Functions - Carpintero, C.; Rosas, E.; Rajesh, N.; Saranyasri, S. (Sarajevo journal of mathematics, 2025)
In this paper we introduce and study a new classes of functions called somewhat $ω$-continuous functions as a generalization of the somewhat continuous functions. 2010 Mathematics Subject Classification. 54B05,54C08.